Development of impulsive discharge in air at one-electron initiation; Proceedings of the IXth International Conference on Phenomena in Ionized Gases, Bucharest, september 1-6, 1969 - Bychkov Ju. I. (1969, 1969)
В фонде НТБ ТПУ отсутствует